Analisis Strategi Pengembangan Wirausaha Pemuda Dalam Mewujudkan Wirausahawan Mandiri dan Implikasinya Terhadap Ketahanan Ekonomi Keluarga Pada Anggota Koperasi Tani dan Nelayan Al Kautsar Gresik - Sutrisno Sutrisno; Dyah Annisa Sari (Yos Soedarso Economic Journal (YEJ), 2020)
Entrepreneurship is a means of overcoming unemployment. Most entrepreneurial activities are also very helpful for businesses in meeting the needs of the community at large. Fostering young entrepreneurs can be one way to help the economy and foster an entrepreneurial spirit as a way out to reduce unemployment because youth are expected to become educated youth entrepreneurs who are able to start their own businesses. To develop a business, entrepreneurs must carry out strategies in full, such as executing targeted marketing and management strategies.The formulation of the problem in this research is: How to analyze youth entrepreneurship development strategies in realizing independent entrepreneurs in the members of the Al Kautsar Farmers and Fishermen Cooperative in Gresikcabang Jati Agung, and what are the implications of youth entrepreneurship development strategies for members of Al Kautsar Gresik Farmers and Fishermen Cooperatives in East Java in an effort to create entrepreneurs. independent family economic resilience. The purpose of this study is to analyze and analyze the development strategy of young entrepreneurs in realizing independent entrepreneurs in the members of the Al Kautsar Gresik Farmers and Fishermen Cooperative in East Java and to see and implement youth entrepreneurship development strategies for the members of the Al Kautsar GresikJ awa Timur Farmers and Fishermen Cooperative in an effort creating independent entrepreneurs to family economic resilience.This research is a field research (field research) using a qualitative descriptive method. The research data collection uses, documentation observation, interviews, questionnaires. Based on the results of the study, it can be denied that the youth entrepreneurship development strategy at the Al Kautsar Gresik Farmers and Fishermen Cooperative, East Java, has not been said to be independent, because entrepreneurs are still afraid to take risks. In carrying out the marketing strategy carried out by entrepreneurs, it is not optimal and lack of management ability becomes an obstacle in realizing independent entrepreneurs. The implications of youth entrepreneurship development strategies in realizing independent entrepreneurs against family economic resilience are said to be sufficient and resilient in meeting daily needs. Constraints in realizing independent entrepreneurs have implications for the economic resilience of the families of youth entrepreneurs in the Al Kautsar Gresik Farmers and Fishermen Cooperative, East Java and also has implications for the development of their business.Keywords: Business strategy; Independent Entrepreneurship; Family Economic Resilience.